Pemetaan Problem Relasi Antar Umat Beragama di Kecamatan Rimba Melintang Kab. Rokan Hilir - Abd. Ghofur (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
The Harmony among religious believers is an important pillar for the realization of the harmony of the nation. Religious harmony is not static, but is dynamic as the dynamics in the religious life.Factors of non-religious often have broad impact, sometimes affecting religious factors, such as religious broadcasting, the establishment of houses of worship, religious splinter, inter-religious marriages, religious education, celebration of religious holidays, and others. This article tries to examine the problem of mapping relations between religious communities in the subdistrict Rimba Rokan Hilir